Determination of the influence of the dose dependence of radiation damage on changes in the thermophysical parameters of oxide ceramics - materials of inert matrices of dispersed nuclear fuel - Kadyrzhanov Д.Б.; Giniyatova Ш.Г.; Zdorovets М.В.; Shlimas Д.И. (Recent Contributions to Physics, 2024)
Interest in the direction of research related to the study of the mechanisms of radiation damage is primarily due to the possibility of obtaining new data on the effect of irradiation of heavy ions on maintaining the resistance of ceramics to damage and deterioration of thermophysical properties, as well as the establishment of the most promising materials for inert matrices, which are one of the options for transition to new types of nuclear fuel, the use of which will improve the operating efficiency of new generation nuclear reactors. Three types of refractory ceramics based on magnesium, tungsten and zirconium oxide were used as objects for research. During the studies, it was found that the reduction in the thermophysical parameters of the studied oxide ceramics is influenced by the amount of accumulated structural distortions associated with the formation of locally isolated defective inclusions in the damaged layer, the accumulation of which, with increasing irradiation fluence, leads to partial amorphization and disordering of the damaged layer. At the same time, for ZrO2, the accumulation of structural distortions, leading to polymorphic transformations, leads to a change in the rate of decrease in thermophysical parameters associated with phase changes (polymorphic transformations of the m – ZrO2 → c – ZrO2 type). In the case of a change in the type of ions during irradiation (during the transition from Kr15+ ions to Xe23+ ions), an increase in the decrease in thermophysical parameters is observed during high-dose irradiation, which in turn is due to the effects of more pronounced structural deformations due to an increase in ionization losses in the material.